Combined central and peripheral demyelination: a case report resembling encephalomyeloradiculoneuropathy - Zhou, Xuan; Peng, Ali; Li, Chuan; Li, Lin; Yao, Dan; Hao, Yunfeng; Zhao, Chao; Yan, Qi; Li, Ying; Liu, Juntong; Liu, Shuyu; Zhu, Wenping; et al. (Frontiers in Neurology, 2024)
Combined central and peripheral demyelination (CCPD) is an extremely rare disease characterized by inflammatory demyelination in both the central and peripheral nervous systems. Herein, we reported case of a 14-year-old teenager who initially presented with the symptoms of acute myelitis (AM). Subsequently, the patient developed symptoms consistent with Guillain-Barré syndrome (GBS), which was supported by nerve conduction studies (NCV) and cerebrospinal fluid (CSF) analysis. Throughout the course of the disease, the patient experienced abdominal pain and abnormal liver function. After a comprehensive evaluation, we determined that the abnormal liver function was a result of hepatitis E virus (HEV) infection, which may have acted as a trigger for GBS. The patient was treated with corticosteroids, intravenous immunoglobulin and Rituximab, resulting in symptom relief and clinical improvement after therapy and follow-up. This case highlights the potential responsiveness and reversibility of CCPD. Given the heterogeneous nature of CCPD, there is currently no standardized diagnostic criteria or clear consensus on its treatment. Therefore, we recommend a thorough assessment of all possibilities and the development of consolidated management guidelines based on available data for this disorder.